Grammatical Error Found in the Academic Essays Written by Students of English Education - Zuvyati A. Tlonaen (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2020)
Writing academically demands students to use correct grammar yet students still make error grammatically. This research reports on grammatical errors in academic essays written by Students of English Education. This study addresses two research questions; 1) What are the grammatical errors made by Students of the English Education Program? 2) From the error classification, what is the major error made? The method used is a qualitative method. The sample subjects were 5 of 15 students writing the essays. They are fifth semester students from English Education study program, Artha Wacana Christian University, Kupang. The samples were determined by purposive sampling. Data was collected using documentation techniques. The results indicated that students have made the grammatical errors in their academic essays. The errors committed by the students are; 1) noun-noun groups, this part consists of four categories, students made error in all categories; 2) Verb-verb groups, this part has nine categories; students committed errors in three categories; 3) Preposition error, this part has three categories. Students made errors in two categories; 4) Sentence structure; this part consists of eight categories. Students made errors in three categories. The major errors committed by the students are; first, in noun-noun groups by using inappropriate combination of subject and verb agreementand omitting the plural marker –s; second, in verb-verb groups in which the errors are mainly in the omission of suffix –s, -es, -ed and the omission of auxiliary verbs. Thus, students of English education need to improve their writing on academic essays.